A probabilistic interpretation of the Miner number for fatigue life prediction (Fracture and Structural Integrity, 2014)
The Miner number M, used as a tool for lifetime prediction of mechanical and structural components in most of the standards related to fatigue design, is generally accepted as representing a damage stage resulting from a linear progression of damage accumulation. Nonetheless, the fatigue and damage approach proposed by Castillo and Fernández-Canteli, permits us to reject this conventional cliché by relating M to the normalized variable V, which represents percentile curves in the S-N field unequivocally associated to probability of failure. This approach, allowing a probabilistic interpretation of the Miner rule, can be applied to fatigue design of mechanical and structural components subjected to variable amplitude loading. The results of an extensive test program on concrete specimens under compressive constant and load spectra, carried out elsewhere, are used. A parallel calculation of the normalized variable V and the Miner number M is performed throughout the damage progression due to loading allowing probabilities of failure to be assigned to any value of the current Miner number. It is found that significant probabilities of failure, say P=0.05, are attained for even low values of M, thus evidencing the necessity of a new definition of the safety coefficient of structural or machine components when the Miner rule is considered. The experimental and analytical probability distributions of the resulting Miner numbers are compared and discussed, the latter still providing a nonconservative prediction in spite of the enhancement. A possible correction is analyzed.
Keywords: Cumulative damage